Gastric tumorigenesis induced by combining Helicobacter pylori infection and chronic alcohol through IL-10 inhibition. (17th December 2021) - Aziz, Faisal; Chakraborty, Abhijit; Liu, Kangdong; Zhang, Tianshun; Li, Xiang; Du, Ruijuan; Monts, Josh; Xu, Gang; Li, Yonghan; Bai, Ruihua; Dong, Zigang
Abstract: Helicobacter pylori infection and alcohol intake are independent risk factors in gastric carcinogenesis; however, until now, the combined effect of H. pylori infection and alcohol consumption and the specific mechanism is still problematic. Here, we developed a series of mouse models that progress from chronic gastritis to gastric cancer, induced by infecting H. pylori combined with chronic alcohol consumption and then determining the molecular mechanism of the progression by flow cytometry, western blotting, qPCR, Mito Traker assay in the gastric cancer and T-cell lines. Interleukin-10 (IL-10) knockout mice was used to determine whether IL-10 deficiency directly contributes to H. pylori and alcohol induced gastric tumorigenesis. Alcohol consumption, together with H. pylori infection, causes gastric cancer; IL-10 downregulation and mitochondrial metabolic dysfunction in CD8 + cells are also involved. IL-10 knockout accelerates tumor development in mice with either H. pylori infection or alcohol induced gastric cancer or both. IL-10 inhibits glucose uptake and glycolysis and promotes oxidative phosphorylation with lactate inhibition. Consequently, in the absence of IL-10 signaling, CD8 + cells accumulate damaged mitochondria in a mouse model of gastric cancer induced with the combination of alcohol plus H. pylori infection, and this results in mitochondrial dysfunction and production of IL-1β. IL-1β promotes H. pylori infection and reduces NKX6.3 gene expression, resulting in increased cancer cell survival and proliferation. Gastric cancer can be induced by the combination of H. pylori infection and chronic alcohol consumption through IL-10 inhibition induced CD8 + cells dysfunction and NKX6.3 suppression. Graphical Abstract: Abstract : Gastric cancer can be induced by combination of Helicobacter pylori infection and chronic alcohol consumption through IL-10 inhibition induced CD8 + cells dysfunction and NKX6.3 suppression.